Efficient Indexation of Social Insurance Pensions - Bartkus, Algirdas (Lithuanian Journal of Statistics, 2010)
This paper tries to formulate conclusions about the indexation of old-age pensions. Pensions can be adjusted and indexed taking into consideration a wage increase. The point of indexation with regard to wages lies in the increment of pensions on to a new, higher nominal level of consumption opportunities (the pension increases), but leaving it at the same relative or potential level of consumption opportunities (the pensions-to-earnings ratio remains constant). Pensions can also be adjusted and indexed according to an increase in the price level. The adjustment of pensions with respect to the price level maintains the real level of consumption (a person is always able to buy the same set of goods). The aim of this study is to identify the conditions of efficient indexation; to summarize the methods of indexation; to draw conclusions as to which of these methods maximizes the wealth of taxpayers.
Keywords: none